Prospek pengembangan sayuran Dataran Rendah di Kabupaten Pelalawan - Rachmiwati Yusuf; Marda Willis; Dahono ' (Jurnal Sagu, 2007)
The research on prospect of increasing of lowland vegetables in Pelalawan District was conducted from Mei to November 2005. The research was aimed to get data and informations on the type of vegetable at lowland with high production and had good marketing prospect. Primary data were obtainedby survey methodwith selected 30 farmer and 20 collected traders using simple random sampling. Result of research show that yard longbean and cucumber had high productions, but kangkong has high procentace sale, while spinach and chines cabbage got high procentace profit.